Study of Biochemical Parameters in Major Thalassemia Patients - Almajidi, Mohammed I.; Hamza, Thulfeqar A. (PROSPECTIVE RESEARCHES, 2024)
Thalassemia is a genetic disorder that affects the production of hemoglobin, the protein that carries oxygen in red blood cells. This disorder alters some blood and biochemical parameters, leading to anemia and other complications. We conducted a study on 120 thalassemia patients from the Thalassemia Center at Baghdad Hospital in Iraq, from April 2022 to March 2023. The patients had an average age of 13 ± 3.5 years. We measured their hematological and biochemical parameters and compared them with healthy controls. We found that the patients had lower levels of red blood cells (RBC), hemoglobin (Hb), and packed cell volume (PCV) than the controls, and higher levels of glutamic-oxaloacetic transaminase (GOT), glutamic-pyruvic transaminase (GPT), alkaline phosphatase, and urea. The differences were statistically significant (P < 0.05). Our study shows the impact of thalassemia on blood and biochemical parameters and highlights the need for effective treatment and management of this disorder.